ZF-CxxC domain-containing proteins, CpG islands and the chromatin connection - Long, H; Blackledge, N; Klose, R (2013)
Vertebrate DNA can be chemically modified by methylation of the 5 position of the cytosine base in the context of CpG dinucleotides. This modification creates a binding site for MBD (methyl-CpG-binding domain) proteins which target chromatin-modifying activities that are thought to contribute to transcriptional repression and maintain heterochromatic regions of the genome. In contrast with DNA methylation, which is found broadly across vertebrate genomes, non-methylated DNA is concentrated in regions known as CGIs (CpG islands). Recently, a family of proteins which encode a ZF-CxxC (zinc finger-CxxC) domain have been shown to specifically recognize non-methylated DNA and recruit chromatin-modifying activities to CGI elements. For example, CFP1 (CxxC finger protein 1), MLL (mixed lineage leukaemia protein), KDM (lysine demethylase) 2A and KDM2B regulate lysine methylation on histone tails, whereas TET (ten-eleven translocation) 1 and TET3 hydroxylate methylated cytosine bases. In the present review, we discuss the most recent advances in our understanding of how ZF-CxxC domain-containing proteins recognize non-methylated DNA and describe their role in chromatin modification at CGIs. © 2013 The Author(s).